Restoring hotel profitability (Caribbean Tourism Organization BridgetownBB, 1995)
Posits that improving the performance and profitability of the hotel sector is key to unlocking its potential for future growth of the tourism industry in the Caribbean. Advises that restoring the competitivenes of the Caribbean hotel sector requires actions on the parts of both the hotels sector and the governments of the region.
DC